Buddhist philosophy : essential readings - Edelglass, William; Garfield, Jay L., 1955- (Oxford University Press, 2009)
Acknowledgments. Table of Contents. Introduction. Part I: Metaphysics and Ontology. 1. Theravada Metaphysics and Ontology: Kaccanagotta (Samyutta-nikaya) and Abhidhammatthasangaha Noa Ronkin. 2. Nagarjuna's Mulamadhyamakakarika (Fundamental Verses of the Middle Way): Chapter XXIV: Examination of the Four Noble Truths, Jay L. Garfield. 3. Vasubandhu's Trisvabhavanirdesa (Treatise on the Three Natures), Jay L. Garfield. 4. Santaraksita's "Neither-One-Nor-Many" Argument from The Ornament of the Middle Way (Madhyamakalamkara): A Classical Buddhist Argument on the Ontological Status of Ph